Performance and carcass characteristics of Chianina-X steers - Riley, Jack G.; Fink, G. (Kansas State University. Agricultural Experiment Station, 2011)
Chianina-X steers gained consistently during a 151-day finishing test and produced high yielding carcasses with 0.06 in. fat and 1.71 square of loin per hundred pounds of carcass. Average USDA quality grade was between high good and low choice.
Keywords: Beef; Performance; Carcass characteristics; Quality grade